LEGAL ASPECTS OF CONSUMER PROTECTION AGAINST PHISHING CRIMES IN DIGITAL BUSINESS - Dahlan; Erniyanti; Henry Aspan; Etty Sri Wahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of digital business in Indonesia has brought significant impacts on the increase of cybercrime, particularly phishing. This research aims to analyze the legal aspects of consumer protection against phishing crimes in the context of digital business in Indonesia with a case study in Medan City. The research method used is normative juridical with statutory and case approaches. The research findings indicate that the legal framework for consumer protection against phishing crimes in Indonesia has been regulated in various regulations, including Law Number 8 of 1999 concerning Consumer Protection, Law Number 19 of 2016 concerning Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions, and Law Number 27 of 2022 concerning Personal Data Protection. However, the implementation of legal protection still faces various obstacles, such as low digital literacy among the public, limited cyber law enforcement infrastructure, and complexity of evidence in phishing cases. This research recommends strengthening more specific regulations regarding phishing, increasing law enforcement capacity, and continuous public education.